(untitled) (African Scientific Reports, 2024)
Studies on aquatic pollution are crucial for maintaining environmental health. This study assessed the toxicity of effluents from the male hostel site II at Delta State University (DELSU) on Oreochromis niloticus fingerlings. Behavioral responses and mortality rates were observed as toxicity indicators. The physicochemical characteristics of the raw effluent were evaluated and compared with standard methods. In a 96-hour static bioassay, 20 fingerlings were exposed to varying effluent concentrations: 0%, 20%, 40%, 60%, 80%, and 100%, with the experiment triplicated. Analysis showed pH (5.6), temperature (26.1°C), TDS (304 mg/L), dissolved oxygen (5.7 mg/L), chlorine (5.55 mg/L), ammonia (0.21 mg/L), and hardness (0.79 mg/L). Water analysis over 12-96 hours ranged for pH (5.45-5.62), temperature (22.50-26.30°C), TDS (61.50-237.50 mg/L), DO (4.45-6.00 mg/L), chlorine (0.84-3.98 mg/L), ammonia (0.14-0.37 mg/L), and hardness (6.52-31.93 mg/L), with no statistically significant differences (p>0.05). Behavioral responses included air gulping, irregular swimming, and lack of reflex. Mortality depended on effluent concentration, with no deaths at 0%-80% but 80% mortality at 100%. Lethal times for 50% and 95% mortality at 100% concentration were 48.6 and 102.8 hours, respectively. Diluting or treating wastewater before release is necessary to prevent fish mortality in the wild.